2003
DOI: 10.12968/bjon.2003.12.sup2.11327
|View full text |Cite
|
Sign up to set email alerts
|

Why patients do not comply with compression bandaging

Abstract: The aim of this study was to explore the perceptions of patients presenting with venous leg ulceration who were labelled as 'non-compliant' with compression bandaging by district nurses. A hermeneutic approach was taken and 14 patients with chronic venous leg ulceration were interviewed. Six themes emerged from the data: (1) lay perceptions of the cause and healing of leg ulceration, (2) concurrent problems of leg ulceration, (3) dilemmas of treatment, (4) perceptions of healthcare professionals, (5) the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 30 publications
0
45
0
6
Order By: Relevance
“…There are patient-related factors that should be considered as they can influence the management of care. These factors should also be acknowledged and addressed by the healthcare provider to ensure that the selected dressing enhances the quality of patient care (Edwards, 2003;Finlayson et al, 2010). The findings of this study clearly demonstrate that dressing selection caused some confusion among CRGNs and PHNs regarding the most appropriate dressing to apply to infected wounds and exudating wounds.…”
Section: Appropriate Use Of Dressingsmentioning
confidence: 81%
“…There are patient-related factors that should be considered as they can influence the management of care. These factors should also be acknowledged and addressed by the healthcare provider to ensure that the selected dressing enhances the quality of patient care (Edwards, 2003;Finlayson et al, 2010). The findings of this study clearly demonstrate that dressing selection caused some confusion among CRGNs and PHNs regarding the most appropriate dressing to apply to infected wounds and exudating wounds.…”
Section: Appropriate Use Of Dressingsmentioning
confidence: 81%
“…A study by Edwards 27 concluded that many patients do not have a clear understanding of their condition or the treatment regimes prescribed. In addition, Edwards 27 indicated that concurrent problems associated with compression bandaging (eg, pain, leakage of exudates, and skin irritation) contribute to nonadherence. In a study by Kiev et al, 28 socioeconomic factors, cosmetic reasons, concerns about discomfort, and difficulty in putting on the stockings were identified as primary reasons for nonadherence.…”
Section: Commentmentioning
confidence: 99%
“…Allodynia is a likely characteristic of neuropathic pain (Wall, 1991); therefore, applying a tight heavily layered bandage can be expected to cause further pain. Others have also reported that patients take off their bandages to reduce discomfort (Edwards, 2003;Herber et al, 2007). Both hyperalgesia and allodynia, if present, would cause a significant amount of pain if a bandage were being applied to the area, regardless of correct or appropriate application.…”
Section: Nature Of Pain Associated With Leg Ulcerationmentioning
confidence: 99%